Pierce’s Analysis On The Billboard Advertisement Of G20’s Bali Indonesia 2022 - Mahmud, Lida Holida; Annisa Rizki Rustam Emelya Gispa (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The purpose of this research is to investigate the semiotics representations that are found at the G20 Bali Bilboard, which are platforms that provide the public with information and support. This study applied Pierce’s theory This study focuses on the symbols, icons, and indexes that are displayed on the billboard for the G20 meeting in Bali. An approach known as qualitative research was utilized for this study, and the results were provided in the form of both visuals and text. Through the use of the images and the wording in the advertisement, analysis was applied to generate a distinct differentiation between symbols, icons, and index. The study found that the meaning of G20’s Bali Billboard advertisement led to invitation to all members of G20 to recover and stronger together after Covid Pandemic, in terms of economics, health, and climate exchange.